2018
DOI: 10.1111/dom.13455
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hepatic glucose production and AMPK by AICAR but not by metformin depends on drug uptake through the equilibrative nucleoside transporter 1 (ENT1)

Abstract: AimRecently we have observed differences in the ability of metformin and AICAR to repress glucose production from hepatocytes using 8CPT‐cAMP. Previous results indicate that, in addition to activating protein kinase A, 8CPT‐modified cAMP analogues suppress the nitrobenzylthioinosine (NBMPR)‐sensitive equilibrative nucleoside transporter ENT1. We aimed to exploit 8CPT‐cAMP, 8CPT‐2‐Methyl‐O‐cAMP and NBMPR, which is highly selective for a high‐affinity binding‐site on ENT1, to investigate the role of ENT1 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, although not significant, AICAR appears to reduce whole body mass loss and does significantly decrease circulating FFAs. Studies have shown that AICAR improves insulin sensitivity as well as glucose uptake and fat oxidation in skeletal muscle while suppressing glucose production in the liver [42], [43]. As such, while this pharmacological agent does not affect the browning of adipose, it may exert downstream benefits via modulation of hyperglycemia/insulin resistance, hallmarks of the hypermetabolic response to severe burn injury [2].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although not significant, AICAR appears to reduce whole body mass loss and does significantly decrease circulating FFAs. Studies have shown that AICAR improves insulin sensitivity as well as glucose uptake and fat oxidation in skeletal muscle while suppressing glucose production in the liver [42], [43]. As such, while this pharmacological agent does not affect the browning of adipose, it may exert downstream benefits via modulation of hyperglycemia/insulin resistance, hallmarks of the hypermetabolic response to severe burn injury [2].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this process became questionable after publication of results showing that AICAR directly inhibits fructose-1,6-bisphosphatase in hepatocytes lacking AMPK [ 29 ]. Despite contradictory results, the latest research seem to support the mutual impact of AICAR and AMPK on hepatic glucose production [ 30 ]. The second group of AMPK activators are compounds binding directly to β subunit of AMPK.…”
Section: Structure and Activation Of Ampkmentioning
confidence: 99%
“…Uridine uptake assay was performed as described [ 48 ]. Briefly, C2C12 myotubes were washed once in uridine uptake buffer (20 mM Tris–HCl, 3 mM KH 2 PO 4 , 1 mM MgCl 2 , 2 mM CaCl 2 , 5 mM glucose, 130 mM NaCl, pH 7.4) before incubating at room temperature in 400 μl uridine uptake buffer containing vehicle (0.1% DMSO), NBMPR, or SBI-0206965.…”
Section: Methodsmentioning
confidence: 99%